Perubahan Kerapatan Vegetasi Kota Kupang Berdasarkan Citra Landsat 8 Tahun 2014-2024 - Manalu, Tugma Jaya; Haryani, Poppy; Sejati, Martina Ayu (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Vegetation change is a key indicator for observing environmental dynamics using GIS and remote sensing approaches. Kupang City as an urban growth center in East Nusa Tenggara, is experiencing development pressures that affect the presence of natural vegetation. This study aims to map vegetation index changes and analyze their dynamics from 2014 to 2024. The method employed NDVI calculation using ArcGIS 10.8 software. The results show that high density vegetation increased from 2,124.9 ha in 2014 to 2,780.46 ha in 2024; medium-density vegetation decreased from 11,133.27 ha to 9,878.49 ha; low-density vegetation increased from 2,269.44 ha to 2,869.65 ha; and non-vegetation areas slightly decreased from 6.75 ha to 5.76 ha. The most significant change occurred in the medium-density class, with a conversion of 1,221.30 ha to low-density vegetation. These findings provide essential insights for vegetation monitoring and sustainable spatial planning in Kupang City.